(untitled) (Journal of Engineering, 2024)
This work investigates individual and social concerns regarding the integral sustainability of an alternative low-carbon cement. The framework of Integral Philosophy was used for the investigation. Social surveys were conducted in Australian, American, and Sri Lankan contexts. The data was collected through both closed-ended and open-ended questions in a questionnaire. Analysis of responses was carried out using fuzzy techniques and grounded theory techniques. Results indicate that individuals and societies in all three countries are more concerned about market price, quality standards, sustainability issues, and recommendations from professionals when selecting a new cement. In all three contexts, they also indicate that there is generally high support among individuals and societies for accepting low-carbon cement as an integrally sustainable cement. Combining the top-down Integral Theory approach with the bottom-up Grounded Theory is a valuable tool for social science research.